Reason as the Ladder to the Divine: Mulla Sadra's Philosophy of the Soul - Hannani, Rohmatul; Soleh, Achmad Khudori (Cakrawala: Jurnal Studi Islam, 2024)
Mulla Sadra's transcendent theosophy, or al-hikmah al-muta’aliyah, offers a unique synthesis of Islamic theology and rational philosophy. This intellectual tradition provides a profound exploration of the human soul, bridging the gap between religious belief and scientific inquiry. This paper delves into Mulla Sadra's conception of the soul, examining its definition, faculties, potentials, and ultimate realization. Through a comprehensive literature review and interpretive analysis, this study reveals that: Mulla Sadra posits the soul as a perfect realization of the body's potentialities, divided into vegetative, animal, and human aspects. The human soul, endowed with reason, seeks knowledge and perfection. This pursuit culminates in the actualization of reason, leading to the soul's ultimate return to its divine source.